1893 Fla. Laws 71, ch. 4147 - (:unkn) unknown (General Publisher, 1893)
Required a license to carry a Winchester or other repeating rifle. Licenses to cost a one hundred dollar bond. Violators shall be guilty of a misdemeanor and a fine not exceeding one hundred dollars or sixty days in jail.
--
Keywords: CARRY